MORPHOLOGY OF LUMPHOID FORMATIONS ASSOCIATED WITH MUCOUS MEMBRANES OF TUBE-LIKE ORGANS OF DOMESTIC SWINE AT EARLY STAGES OF POSTNATAL PERIOD OF ONTOGENESIS - Панікар, І. І. (Scientific Progress & Innovations, 2015)
It has been found out that morphological features of the development of lymphoid formations associated with mucous membranes of tube-like organs are connected with their topography and they are the criteria to evaluate the state of non-specific and specific immune reactivity of the pig’s body. Their cytostructure is represented by the population of relevant cellular elements. The dynamics of the relative area of the lymphoid patches varies irregularly: it increases in the anterior and medium parts of the jejunum up to the age of 14th day and in the posterior part – till the age of 7th day and then gradually decreases till the age of 29th day.